1975
DOI: 10.1007/bf00428901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of p-chlorophenylalanine on the acquisition of tolerance to ethanol and pentobarbital

Abstract: Rats were rendered tolerant to ethanol or pentobarbital by daily oral administration. Motor impairments after test doses of ethanol or pentobarbital were measured prior to and at various times during chronic treatment in order to assess the degree of tolerance development. Chronic administration of p-chlorophenylalanine (p-CPA) in a dosage regimen which produced and maintained approximately 95% depletion of brain serotonin (5-HT) did not alter motor impairment after initial acute administration of ethanol or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

1977
1977
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…A long history of research using animal models has reported a role for the serotonin system in regulating virtually every aspect of the progression to alcohol dependence, including intake, preference, tolerance, and withdrawal (Myers and Veale, 1968; Griffiths et al, 1974; Frankel et al, 1975; Richardson and Novakovski, 1978). Despite an abundance of studies, the relationship between ethanol and serotonin remains unclear (for review LeMarquand et al, 1994; Kenna, 2010; Sari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A long history of research using animal models has reported a role for the serotonin system in regulating virtually every aspect of the progression to alcohol dependence, including intake, preference, tolerance, and withdrawal (Myers and Veale, 1968; Griffiths et al, 1974; Frankel et al, 1975; Richardson and Novakovski, 1978). Despite an abundance of studies, the relationship between ethanol and serotonin remains unclear (for review LeMarquand et al, 1994; Kenna, 2010; Sari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…1979]. Similarly, ad ministration of L-tryptophan [Z.i>etal., 1979] or task performance under the influence of ethanol [LeBlancet al" 1976] accelerated the acquisition of ethanol tolerance in rats, while treatment with p-chlorophenylalanine slow ed the development of tolerance [Frankel et al, 1975].…”
Section: Discussionmentioning
confidence: 99%
“…The state of isolation represents a whole spectrum of physiological changes. Among them is a decrease in adrenal size and plasma corticosterone level [Louch and Higginbo tham, 1967], Changes in brain neurotrans mitter metabolism have also been investi gated, including changes in the turnover rate of brain serotonin [Garattini et al" 1967;ValzelU and Bernasconi, 1979] and catechol amines [Garattini et al, 1969;Welch and Welch, 1971], Several studies have shown that brain serotonergic and noradrenergic mechanisms are involved in the develop ment of ethanol tolerance [Frankel et al, 1975[Frankel et al, , 1978Ritzmann and Tabakoff, 1976;Sze, 1977], Therefore, further studies which will tie the isolation-induced neurochemical events and the tolerance changes in causal relationship seem pertinent. Such studies will contribute to our understanding of the mech anisms mediating the development of alco hol tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The first evidence that chronic consumption of ethanol and the development of tolerance to the effects of ethanol in animals might have to do with 5-HT neurotransmission was provided by Frankel et al (1975). These authors have shown that inhibition of 5-HT synthesis by p-chlorophenylalanine impaired the acquisition of tolerance to the effects of ethanol.…”
Section: Animal Studiesmentioning
confidence: 99%